АБАЙ ШЫҒАРМАЛАРЫНДАҒЫ АДАМГЕРШИЛИК ПАЗЫЙЛЕТЛЕРДИҢ БИЙБАҲАЛЫҒЫ - Салқынбай, А.Б. (ILIM hám JÁMIYET, 2025)
The article outlines the views of Abay Kunanbayev, the brilliant poet of the Kazakh people, on national values. From a scientific point of view, the influence of Abai’s philosophical worldview on the consciousness of the Kazakh nation has been studied, and specific examples from the poet’s poems have been given. Abai’s personal thoughts and opinions about the place of the individual in society will also be discussed and analyzed.